Factors of Selecting Accommodation for Tourists - Nurmaiza Rosaliya Ab Manab; Nurainin Sofia Kamarudin (CSR International Journal, 2023)
Accommodation is one of the most important things when we go travelling because it is a place for us to stay throughout the vacation. Some people did a lot of research just to find a good place to stay. Besides that, the objective of this research is to find the biggest factors for tourists when choosing a place to stay. Then, the respondents were asked three main factors when selecting an accommodation, which are comfort, price and facilities of the accommodation. In this research, quantitative techniques were used in asking questions to the respondents through questionnaires when collecting the data. The results show that a few factors were important for tourists when selecting a place to stay.